Dual inhibition of MEK1/2 and MEK5 suppresses the EMT/migration axis in triple‐negative breast cancer through FRA‐1 regulation. Issue 8 (20th April 2021) - Hoang, Van T.; Matossian, Margarite D.; La, Jacqueline; Hoang, Kristine; Ucar, Deniz A.; Elliott, Steven; Burks, Hope E.; Wright, Thomas D.; Patel, Saloni; Bhatt, Akshita; Phamduy, Theresa; Chrisey, Douglas; et al.
Abstract: Triple‐negative breast cancer (TNBC) presents a clinical challenge due to the aggressive nature of the disease and a lack of targeted therapies. Constitutive activation of the mitogen‐activated protein kinase (MAPK)/extracellular signal‐regulated kinase (ERK) pathway has been linked to chemoresistance and metastatic progression through distinct mechanisms, including activation of epithelial‐to‐mesenchymal transition (EMT) when cells adopt a motile and invasive phenotype through loss of epithelial markers (CDH1), and acquisition of mesenchymal markers (VIM, CDH2). Although MAPK/ERK1/2 kinase inhibitors (MEKi) are useful antitumor agents in a clinical setting, including the Food and Drug Administration (FDA)‐approved MEK1, 2 dual inhibitors cobimetinib and trametinib, there are limitations to their clinical utility, primarily adaptation of the BRAF pathway and ocular toxicities. The MEK5 (HGNC: MAP2K5) pathway has important roles in metastatic progression of various cancer types, including those of the prostate, colon, bone and breast, and elevated levels of ERK5 expression in breast carcinomas are linked to a worse prognoses in TNBC patients. The purpose of this study is to explore MEK5 regulation of the EMT axis and to evaluate a novel pan‐MEK inhibitor on clinically aggressive TNBC cells. Our results show a distinction between the MEK1/2 and MEK5 cascades in maintenance of the mesenchymal phenotype, suggesting that the MEK5 pathway may be necessary and sufficient in EMT regulation while MEK1/2 signaling further sustains the mesenchymal state of TNBC cells. Furthermore, additive effects on MET induction are evident through the inhibition of both MEK1/2 and MEK5. Taken together, these data demonstrate the need for a better understanding of the individual roles of MEK1/2 and MEK5 signaling in breast cancer and provide a rationale for the combined targeting of these pathways to circumvent compensatory signaling and subsequent therapeutic resistance. Abstract : Dual inhibition of the MEK1/2 and MEK5 signaling pathways suppressed triple‐negative breast cancer cell migration, mesenchymal features, and metastasis. Mechanistically, MEK1/2 and MEK5 function through FRA‐1 activity to exert the observed pro‐migratory and mesenchymal phenotypes.